STRUCTURAL DYNAMICS OF FREE MOLECULES AND CONDENSED MATTER. Part I. THEORY AND EXPERIMENTAL TECHNIQUE - A. A. Ischenko; Y. I. Tarasov; L. Schäfer (Тонкие химические технологии, 2017)
To understand the dynamic features of molecular systems with a complex landscape of potential energy surfaces, it is necessary to study them in the associated 4D space-time continuum. The introduction of time in the diffraction methods and the development of coherent principles of the research process opened up new approaches for the study of the dynamics of wave packets, intermediates and transient states of the chemical reactions, short-lived compounds in the gaseous and condensed media. Time-resolved electron diffraction, the new method for the structural dynamic studies of free molecules, clusters and condensed matter, differs from the traditional method of electron diffraction both in the experimental part and in the theoretical approaches used in the interpretation of diffraction data. Here there is particularly pronounced the need of a corresponding theoretical basis for the processing of the electron diffraction data and the results of spectral investigations of the coherent dynamics in the field of intense ultrashort laser radiation. Such unified and integrated approach can be formulated using the adiabatic potential energy surfaces of the ground and excited states of the systems under study. The combination of state-of-the-art optical techniques and electron diffraction methods based on different physical phenomena, but complementing each other, opens up new possibilities of the structural studies at time sequences of ultrashort duration. It provides the required integration of the triad, "structure - dynamics - functions" in chemistry, biology and materials science.